Synthetic biology as a building block for circular Bioeconomy: a case study of Chitin - Ahmad Fuad, Fazia Adyani; Tanbin, Suriyea; Azizi, Nur Aqilah Husna; Tengku Abdul Rashid, Tengku Rogayah; , (Springer Nature, 2024)
Synthetic biology has revolutionized many aspects of life, by engineering organisms to have new abilities to be applied for practical uses. Among the fields that benefit most from the advent of synthetic biology is the pharmaceutical field, notably drug discovery. The drug discovery pipeline is known to take over a decade to reach the market, however, with the aid of synthetic biology, the process may well be sped up to completion. This chapter discusses an important aspect of synthetic biology that serves as the basis of circular bioeconomy from a pharmaceutical point of view, which is in silico approach to study protein-drug interactions in novel drug development. This revolves around the analyses of chitin, which is a naturally occurring compound and a biodegradable polymer that has potential as pharmaceutical products and potent drugs that can be obtained at low cost from food and forestry waste, respectively.